Children’s Character Education Values Based on Asy- Sya’rawi’s Exegesis of Surah al-Qalam - Fath, Amir Faishol (TA`DIBUNA, 2025)
This study aims to extract and analyze the values of character education contained in Surah al-Qalam based on the interpretation of Shaykh Muhammad Mutawalli Asy-Sya’rawi and to examine their relevance to contemporary character education, particularly in the role of parents. Employing a qualitative literature-based method with a thematic exegesis (tafsir maudhu‘i) approach, the study identifies core values such as patience, integrity, humility, and steadfastness, which align with the principles of akhlāq al-maḥbūbah (beloved character) and qudwah ḥasanah (good example) in Islamic pedagogy. Practically, the research formulates concrete steps for parents, including protecting children from harmful environments, fostering self-confidence, instilling moral principles, using storytelling as a value-education method, nurturing the spirit of worship, and guiding patience in obedience and da’wah. The findings fill a gap in the literature by providing an in-depth analysis of Surah al-Qalam through the lens of contemporary exegesis, offering an applicable model that bridges Qur’anic values with real-world character-building strategies.Keywords: Character Education, Asy-Sya’rawi’s Tafsir, Parental Role, Islamic Values.AbstrakPenelitian ini bertujuan mengekstraksi dan menganalisis nilai-nilai pendidikan karakter dalam Surah al-Qalam berdasarkan tafsir Syekh Asy-Sya’rawi, serta mengkaji relevansinya bagi pendidikan karakter kontemporer, khususnya dalam peran orang tua. Menggunakan metode kualitatif berbasis literatur dengan pendekatan tafsir tematik (maudhu‘i), penelitian ini mengidentifikasi nilai inti seperti kesabaran, integritas, kerendahan hati, dan keteguhan, yang selaras dengan prinsip akhlāq al-maḥbūbah dan qudwah ḥasanah dalam pedagogi Islam. Secara praktis, penelitian ini merumuskan langkah konkret bagi orang tua, meliputi perlindungan anak dari lingkungan buruk, pembentukan kepercayaan diri, penanaman prinsip moral, penggunaan metode cerita untuk pendidikan nilai, penumbuhan semangat ibadah, serta pembimbingan kesabaran dalam ketaatan dan dakwah. Hasil kajian ini mengisi kesenjangan literatur dengan memberikan analisis mendalam Surah al-Qalam melalui perspektif tafsir kontemporer, sekaligus menawarkan model aplikatif yang menjembatani nilai-nilai Qur’ani dengan strategi pembinaan karakter di dunia nyata.